Impact of consumer awareness and behavior on business exits in the hospitality, tourism, entertainment, and culture industries under the COVID-19 pandemic - Hiroyuki Okamuro; Yasushi Hara; Yunosuke Iwaki (Administrative Sciences, 2022)
Empirical studies on small business survival and exits focus on endogenous firms and top manager characteristics, whereas few studies consider exogenous demand shocks and local consumer awareness and behavior, which are especially important for local hospitality industries. Therefore, this study addresses this research gap by targeting the COVID-19 pandemic and anti-contagion policies as a local demand shock for service industries. We empirically investigate the causal effects of changing local consumer awareness and behavior under COVID-19 on business exits at the prefecture-industry level. Based on a panel fixed-effect estimation using a longitudinal dataset of 32 service industries in 47 prefectures over 10 months in Japan, we demonstrate that an increase in consumers' risk aversion and sympathy for self-restraint from going out, and a decrease in going out with family members, significantly increase the exit ratio in specific service industries in the same prefecture. Moreover, we find that these effects vary by consumer type depending on factors such as gender, age, income level, and household structure.
Keywords: 350; business exit; consumer awareness; COVID-19; demand shock; service industry